Cuprizone Intoxication Results in Myelin Vacuole Formation - Joost, Sarah; Schweiger, Felix; Pfeiffer, Friederike; Ertl, Carolin; Keiler, Jonas; Frank, Marcus; Kipp, Markus (Frontiers in Cellular Neuroscience, 2022)
Myelin damage is a histopathological hallmark of multiple sclerosis lesions. Results of post mortem studies suggest that impaired myelin-axon interaction characterized by focal myelin detachments is an early event during lesion genesis. In this study, we investigated the ultrastructural changes of the axon-myelin interface in the cuprizone model using serial block face scanning electron microscopy and immunohistochemistry. We show that non-inflammatory injury of oligodendrocytes by cuprizone intoxication results in myelin vacuole formation and axonal swellings, paralleled by early alterations of the node of Ranvier cytoarchitecture. This remarkable resemblance of ultrastructural myelin characteristics in multiple sclerosis and the cuprizone animal model suggests that the cuprizone model is a valuable tool to study early pathologies during lesion formation.